2020
DOI: 10.3390/geriatrics5040080
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Diseases and Driving Safety

Abstract: Due to demographic changes, the number of older drivers is steadily increasing. Mobility is highly relevant for leading an independent life in the elderly. It largely depends on car driving, which is a complex task requiring a multitude of cognitive and motor skills vulnerable to age- related functional deterioration. The almost inevitable effects of senescence may be potentiated by age-related diseases, such as stroke or diabetes mellitus. Respective pharmacological treatment may cause side effects, additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 195 publications
(330 reference statements)
0
18
0
Order By: Relevance
“…Previous literature has suggested that advanced age itself is a risk factor for road traffic crashes [ 17 ]. In addition, a wide variety of mental and physical dysfunctions inevitably observed during aging has been proven to yield a high incidence of road traffic crashes [ 6 ]. More specifically, dysfunctions in the sensory system (visual and auditory), central nervous system (stroke, depression, dementia, Parkinson’s disease, and insomnia), cardiovascular system (arterial hypertension, arrhythmia, coronary heart disease, and heart failure), musculoskeletal system (osteoarthritis and rheumatoid arthritis), diabetes mellitus, and polypharmacy as a consequence of the above potentially threatening traffic safety.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous literature has suggested that advanced age itself is a risk factor for road traffic crashes [ 17 ]. In addition, a wide variety of mental and physical dysfunctions inevitably observed during aging has been proven to yield a high incidence of road traffic crashes [ 6 ]. More specifically, dysfunctions in the sensory system (visual and auditory), central nervous system (stroke, depression, dementia, Parkinson’s disease, and insomnia), cardiovascular system (arterial hypertension, arrhythmia, coronary heart disease, and heart failure), musculoskeletal system (osteoarthritis and rheumatoid arthritis), diabetes mellitus, and polypharmacy as a consequence of the above potentially threatening traffic safety.…”
Section: Discussionmentioning
confidence: 99%
“…According to a Japanese observational study, pre-frailty/frailty individuals were highly at risk of experiencing road traffic crashes in the past year compared with robust individuals (OR: 3.74, 95% CI: 1.75–7.96) [ 24 ]. However, a recent review article did not show the clear relationship between road traffic crashes and sarcopenia [ 6 ]. The prevalence of medical factors in the present study was as follows: polypharmacy, 27.6%; dementia, 16.4%; and frail, 15.0%, indicating that older adults with medical factors are driving on a daily basis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher rates of crashes among older adult drivers compared to younger adults are thought to be at least partially influenced by physical and cognitive changes that accompany aging, such as vision, reaction time, and attention [51][52][53]. These changes are even more pronounced among persons with early symptomatic [54] and preclinical [36,[55][56][57][58] AD and may interact with the increasingly complex in-vehicle environment.…”
Section: Interactions Between Driver Characteristics and The In-vehic...mentioning
confidence: 99%
“…There is a growing number of individuals driving cars in urban areas, especially older adults 2 , and with the constant increase in the geriatric population, the number of older adults obtaining a driver's license has increased 3 . However, age-related cognitive decline affects driving abilities and may increase the number of traffic violations and accidents 4 .…”
Section: Introductionmentioning
confidence: 99%